Modeling and implementation of a digital twin of material flows based on physics simulation. (January 2021) - Glatt, Moritz; Sinnwell, Chantal; Yi, Li; Donohoe, Sean; Ravani, Bahram; Aurich, Jan C.
Highlights: Physics simulation is used to create a digital twin of a material handling system. The implementation allows prediction, monitoring and diagnosis functions. Material flows can be performed faster while reducing the risk of disturbances. UML proved to be a valuable modeling approach to ensure a successful implementation. Using the communication protocol OPC UA ensures industrial applicability. Abstract: Cyber-physical production systems enable adaptivity and flexibility when manufacturing customized products in small batches. Due to varying routes and a high variance of workpieces, material flows in cyber-physical production systems can get highly complex, which can lead to physically induced disturbances that can result in accidents or decreased throughput and high costs. This issue can be addressed by applying a physics engine to simulate the physical interaction between workpieces and the material handling systems during the operation. Connecting such a digital model to a real material handling system in order to derive simulation-based decision support leads to the concept of digital twins. To date, few practical implementations of digital twins in manufacturing outside the machine tool domain were reported. Therefore, this paper describes the modeling and the subsequent implementation of an integrated system that consists of a real material handling system and its digital twin, based on physics simulation. A practical use case demonstrates the versatile advantages of the implemented solution for a manufacturing system with respect to the three digital twin functions prediction, monitoring and diagnosis.